Remarks at Opening Press Conference, IMF/World Bank Annual Meetings, Washington, D.C., October 9, 2014 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses the need for more trained health workers in the countries most-affected by Ebola, the Global Infrastructure Facility, and fight against cholera in Haiti. The World Bank Group is pledging $50 million to help improve access to safe water and sanitation for all Haitians, aimed at preventing waterborne diseases.